Studies on the Solubilisation of Iron in Submerged soils and methods to Minimise its Solubility and Toxic concentration to Paddy - Ramasubramonian P R (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
A study has been made of the extent of solubilisation of iron in the submerged acid rice soils of Kerala State where iron toxicity is likely to be a serious field problem during rice cultivation. The kayal, kari and karapadom soils of Kuttanad, brown hydromorphic soils of the midland lateric zone and the sandy soils of Onattukara were included in the study. Chemical characterisation of the soils and soil profiles in relation to forms of iron were investigated with a view to obtain a better understanding of the dynamic aspects of iron in these soils. The nature, and extent of periodical variations in soluble iron as influenced by levels of sea water, organic matter (farm yard manure) and ammonium sulphate added to kayal, kari, karapadom and brown hydromorphic soils under submerged conditions were also studied along with the influence of levels of applied lime on the amelioration of iron toxicity. Among the Kuttanad soils, kari soil was most acidic with a mean pH of 3.77, high organic carbon content and CEC compared to others. The water soluble iron ranged from 79 – 165 ppm in the Kuttanad soils. This form of iron and pH were negatively correlated. Electrical conductivity and water soluble iron were significantly and positively correlated. The exchangeable iron varied between 144 – 310 ppm and was positively correlated with CEC. Active iron ranged between 1460 and 5200 ppm. Active iron had a significant positive correlation with organic carbon and electrical conductivity. Kuttanad soils contained high contents of water soluble and exchangeable iron, together known to contribute towards the development of iron toxicity to transplanted rice in these soils. High contents of water soluble, exchangeable and active iron were noticed in the profiles of Kuttanad soils as well. Compared to these, the brown hydromorphic and sandy (Onattukara) soils had much lower contents of soluble iron. Total iron content decreased with depth in most of the profiles while water soluble, exchangeable and active iron, increased with depth studied upto 100cm. In brown hydromorphic soil the water soluble and exchangeable iron were found to decrease with depth. Incubation studies under laboratory conditions indicated that submergence of soils resulted in an increase in the soluble iron with time, reached a peak value on the 10th day in kari soil and 25th day in the other soils, after which the soluble Fe2+ decreased to lower values. Sea water submergence resulted in enhanced releases of Fe2+ with time to reach peak value around the 25th day followed by decrease. Kayal soil alone, however, needed 40 days for peak release of Fe2+. The release of Fe2+ was influenced by the dilution of sea water used. Kayal, kari and karapadom soils released significantly higher amounts of Fe2+ compared to brown hydromorphic soils. However, at the lowest level of 25 per cent sea water all soils behaved similarly. Presence of organic matter under the submerged conditions enhanced the Fe2+ release considerably depending on the content of organic matter in the soil. Kari soil on the 25th day and kayal soil on the 40th day of submergence released significantly higher amounts of Fe2+. Addition of ammonium sulphate to soils under submerged conditions resulted in increased releases of Fe2+ in the soil solution with time. Peak releases of Fe2+ were noticed on the 25th day in all the soils. Maximum release by kari soil was influenced by ammonium sulphate applied at 100 kg N/ha, in the karapadom and brown hydromorphic soils by 200 kg N/ha. The beneficial effect of lime on the suppression of iron release was clearly evident in the soils though to varying extents. In kayal soil 600 kg lime/ha suppressed iron release upto 10 days and 1000 kg/ha could suppress more soluble iron for 25 days. However, after the 40th day, soluble iron exceeded that of the control. In kari soil the iron suppressing effect of both the levels of lime was evident only up to the 10th day after which the release of soluble iron exceeded that of the control. In karapadom and brown hydromorphic soils, lime at 600 kg/ha was helpful in suppressing the release of Fe2+ till the 40th day. Lime at 1000 kg/ha, however, could suppress more of the soluble Fe2+ throughout the period of submergence. In kayal and kari soils, levels of lime upto 1000 kg/ha appear to be inadequate in controlling iron toxicity. Flooding the field for 25 days and leaching out the released Fe2+ just before planting of rice is suggested as an alternate solution to minimise iron toxicity to rice in Kuttanad soils.